Ensino remoto na pandemia: desafios na adoção das tecnologias por professores na E.E.E. Médio Júlio de Castilhos em Santana do Livramento-RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present work has as its general theme the challenges in the adoption of social networks encountered by teachers in pandemic time. The challenges that the population encountered as a result of the pandemic of the new Coronavirus ended up affecting various sectors of society, especially education, more than two-thirds of students in the world suffered from problems in their learning teaching process, lack of access, levels of social inequality in the sector and lack of support for students and exclusively teachers. Faced with the problem, the objective was to verify the challenges faced by teachers in the pandemic period. In order to make these recent research data relevant in the understanding that the main results show that teachers have adapted even facing some challenges in the adoption of social networks to serve their students during the pandemic period, thus seeking to innovate and lead the best in the contribution of understanding that this type of teaching is not completely replaced but that education had to reinvent itself in order to help the new mode of teaching and learning.
Remote education in pandemic: challenges in the adoption of virtual social networks by teachers in state public school
Keywords: Ensino remoto emergencial; Professores de rede pública; Educação na pandemia; Emergency remote teaching; Public school teachers; Education in the pandemic; CNPQ::CIENCIAS SOCIAIS APLICADAS